Effects of chronic betaine supplementation on exercise performance: Systematic review and meta-analysis. - Zawieja, Emilia; Machek, Steven; Zanchi, Nelo Eidy; Cholewa, Jason; Woźniewicz, Małgorzata (Journal of Sports Sciences, 2024)
Betaine supplementation, a dietary practice that possesses potential effects on exercise performance, has undergone extensive study. This study aimed to systematically review and meta-analyse betaine supplementation's effects on exercise performance. We searched PubMed, Web of Science, Scopus, and Google Scholar, focusing on studies comparing chronic betaine to a placebo in healthy humans aged 15–60 years, measuring exercise outcomes. Studies with acute betaine supplementation, no control group, or animals were excluded. Quality assessment was done using the Cochrane Risk of Bias Tool, and a random-effects model was employed for the meta-analysis. The review included 17 studies with 317 participants (21% female). The results revealed a significant effect size of 0.47 (95% CI 0.04 to 0.89) for maximal strength (1RM, 3RM, maximal isokinetic or isometric force), particularly in the lower body (SMD: 0.49, 95% CI 0.01 to 0.98). No significant effects were found for upper body strength, cycling sprint power, bench press throws power, or muscular endurance. However, vertical jumping performance improved significantly (SMD: 0.36, 95% CI 0.03 to 0.69) after excluding a low-quality study. In conclusion, betaine supplementation for at least 7 days significantly enhances muscular strength, especially lower body strength, and shows potential in improving vertical jumping performance.